2011
DOI: 10.1371/journal.pone.0021726
|View full text |Cite
|
Sign up to set email alerts
|

NFκB1 and NFκBIA Polymorphisms Are Associated with Increased Risk for Sporadic Colorectal Cancer in a Southern Chinese Population

Abstract: BackgroundNuclear factor κB (NFκB) plays a key role in the regulation of apoptosis. The function of NFκB is inhibited by binding to NFκB inhibitor (IκB), and disruption of the balance of NFκB and IκB is related to the development of many diseases, including tumors. Therefore, we hypothesized that the NFκB1 (-94del/insATTG) and NFκBIA (2758 A>G) polymorphisms were associated with colorectal cancer (CRC) susceptibility.MethodsIn a hospital-based case–control study of 1001 CRC patients and 1005 cancer-free contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…Combining multiple variants may result in greater predictive power of disease risk. Song et al [39] have found that combined genotype of ins/ins+del/ins and GG was associated with an increased risk of sporadic cancer, and as shown in the previously published research, ins/ins/AG combine genotype has a protective role on another inflammatory disease, Hashimoto thyroiditis [27]. On the contrary, according to the multiple comparisons of combined genotypes of rs28362491 and rs696, ins/ins/AA combined genotype frequency was significantly higher in patients with BD than in control groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Combining multiple variants may result in greater predictive power of disease risk. Song et al [39] have found that combined genotype of ins/ins+del/ins and GG was associated with an increased risk of sporadic cancer, and as shown in the previously published research, ins/ins/AG combine genotype has a protective role on another inflammatory disease, Hashimoto thyroiditis [27]. On the contrary, according to the multiple comparisons of combined genotypes of rs28362491 and rs696, ins/ins/AA combined genotype frequency was significantly higher in patients with BD than in control groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ins allele was reported to increase the risk of oral cancer,31 melanoma,32 prostate cancer,16 gastric cancer,17 nasopharyngeal carcinoma33 and cervical cancer 34. Two studies in European population found that del allele might increase the risk of colorectal cancer,35 36 while in Chinese population, none or even reverse association was obtained 35 37. The difference of polymorphisms may probably result from interactions or combined effects with non-genetic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Combining multiple variants may result in greater predictive power of disease risk. Song et al have stated that combined genotype of ins/ins+del/ins and GG was associated with the risk of sporadic cancer and as shown in previously published research, ins/ins+AG combined genotype and also ins allele frequencies were higher in BD patients considerably [84]. (51) 61 (41) 12 (8) 98 (70) 31 (21) 12 (9) 0.001 rs7527192 60 (40) 81 (54) 9 (6) 75 (53) 62 (44) 4 (3) 0.042 rs2793378 60 (40) 65 (43) 25 (17) 62 (44) 62 (44) 17 (12) >0.05 rs28362491 50 (27) 113 (69) 27 (14) 26 (22) 76 (63) 18 ( Behcet's Disease rs28362491 50 (27) 113 (59) 27 (14) 43 (48) 38 (43) 8 (9) 0.003 rs696 25 (14) 130 (68) 34 (18) 18 (20) 38 (43) 33 ( Table 2: Allele assessment of SNPs rs1136410, rs7527192, rs2793378, rs28362491, and rs696 in PARP-1 and NFKB1 genes in autoimmune diseases in Turkish population.…”
Section: Behçet's Diseasementioning
confidence: 68%